a integración vertical en la ferretería Zou Ho como mecanismo para la reducción de costos de transacción, Balzar provincia del Guayas, año 2014 - Zou Li, Susana Miley (2015)
The present research was conducted in the city of Balzar, whose head is between Daule and Colimes streets, located in the northeast of the province of Guayas, its geographical coordinates are: 1º21'36 "south latitude and 79º54'0" in length west. The goal of vertical integration is to incorporate Hardware - Machine Shop, as today in the city of Balzar there are five business Hardware that moves the economy of this canton, but many of them are inefficient and do not have this service. The motivation to create this incorporation is because there is a market for motorcycles, repair and supply of spare parts becomes a problem for customers who have to travel Canton looking for an efficient solution. In economic literature proposals for vertical integration between large companies is tested, but not small businesses. However in large markets of Ecuador, as Guayaquil and Quito integrated business evolution is observed, such as: craft workshops, restaurants, etc. integrating the manufacturing part of the packaging and direct distribution. This experience is in the canton Balzar expose and analyze from the administrative and economic science the feasibility of its implementation, the theme consists of the following chapters: In his first chapter deals with the contextual framework of the investigation, where the introduction of this thesis is detailed, problems arise the same as the objectives and hypotheses raised. The second chapter contains the theoretical framework of the research, which details several authors scientifically, conceptual foundation that contributes to the development of this study. The third chapter is composed of the research methodology, which emphasizes the materials and methods in conjunction with the techniques and tools that allow analyzing the problem of the study. The fourth chapter is constituted with the results of research and activities related to studies that demand the execution of the same. The fifth chapter is defined by the conclusions and recommendations of this research. Finally we conclude with the literature that covers research and exhibits related to the study.